COTTON PICKER SPINDLE SPRING CONSTRUCTION - K. Madumarov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article offered method of making of springof of working organ of cotton-picking vehicle.